Edukasi Fisioterapi untuk Manajemen Inkontinensia Urin pada Ibu-Ibu Pasca Melahirkan di Posyandu Asparaga - Maulida Rahma Kurnia; Dimas Sondang Irawan; Gamar (Health Care : Journal of Community Service, 2025)
Urinary incontinence is an involuntary leakage of urine commonly experienced by postpartum women due to pelvic floor muscle weakness. This condition can interfere with daily activities and reduce quality of life. Physiotherapy serves as an effective non-pharmacological approach for the prevention and management of urinary incontinence, particularly through pelvic floor muscle exercises such as Kegel exercise and its variations. This educational activity aimed to improve the understanding of postpartum women at Posyandu Mulyorejo Asparaga RW 4 regarding the prevention and management of urinary incontinence through physiotherapy-based exercises. The study employed a one-group pre–post test design, in which participants completed questionnaires before and after the educational intervention to assess program effectiveness. Educational materials were delivered using leaflets and practical demonstrations of pelvic floor muscle exercises, including classic Kegel exercise, half squat, bridge exercise, cat–cow stretch, cross-legged breathing, and supine relaxation. Post-test results showed a significant increase in participants’ understanding, with all respondents providing correct answers to every post-test question. The physiotherapy education program proved effective in enhancing awareness and skills among postpartum women to independently perform pelvic floor muscle exercises at home as a non-pharmacological strategy to prevent and reduce symptoms of urinary incontinence.